Perceraian Disebabkan Perselingkuhan (Studi Kasus Satu Keluarga di Kelurahan Oesapa Kupang) - Imam Faishol; Fitriana Azzahrah (Prodi Hukum Ekonomi Syariah (Muamalah), 2022)
This research is motivated by the life of a family who does not get a living physically and mentally for approximately 9 years due to the husband having an affair and leaving his house. This research is a qualitative field research with analytical descriptive research methods based on the theoretical basis of the problem by collecting research data using interview techniques to informants, then the data that has been collected is processed by editing and analyzed based on a review of Islamic law. The final conclusion from the research on divorce due to infidelity are: The factors that cause infidelity are frequent fights, boredom, living far apart, the presence of other women, no mutual attention. A review of Islamic law regarding divorce due to infidelity that is not in accordance with Islamic law, in infidelity there are many things that are contrary to Islam and cheating is prone to adultery, from adultery all bad things begin.